A randomized, open‐label, phase I/II trial to investigate the maximum tolerated dose of the Polo‐like kinase inhibitor BI 2536 in elderly patients with refractory/relapsed acute myeloid leukaemia. (16th August 2013) - Müller‐Tidow, Carsten; Bug, Gesine; Lübbert, Michael; Krämer, Alwin; Krauter, Jürgen; Valent, Peter; Nachbaur, David; Berdel, Wolfgang E.; Ottmann, Oliver G.; Fritsch, Holger; Munzert, Gerd; Garin‐Chesa, Pilar; et al.
Summary Polo‐like kinases (Plks) play an important role in cell cycle checkpoint controls and are over‐expressed in acute myeloid leukaemia (AML). BI 2536, a novel Plk inhibitor, induces mitotic arrest and apoptosis. In this phase I/II trial of BI 2536 in 68 elderly patients with relapsed/refractory AML, three schedules were investigated (day 1, days 1–3, and days 1 + 8). Maximum tolerated dose was 350 and 200 mg in the day 1 and days 1 + 8 schedules, respectively. The day 1–3 schedule appeared equivalent to the day 1 schedule and was discontinued early. BI 2536 exhibited multi‐compartmental pharmacokinetic behaviour. The majority of patients showed an increase of bone marrow cells in G2/M with a characteristic pattern of mitotic catastrophe. The overall response rate in the day 1 and day 1 + 8 schedules was 9% (5/54) with 2 complete and 3 partial responses. The majority of drug‐related adverse events grade ≥3 were haematological. Taken together, Plk inhibition induced cell cycle arrest in AML blasts in vivo and BI 2536 monotherapy showed modest clinical activity in this poor prognosis patient group.